A case of cas bubble disease in mature rainbow trout - ΠΑΠΑΘΕΟΔΩΡΟΥ, Β. (Journal of the Hellenic Veterinary Medical Society, 2019)
Cas bubble disease causes severe losses to fishes and especially to varions species of the Salmonids family. Thousands of trouts and salmons die every year, from this disease. It appears especially in fish hatcheries taking the food from sources with apparently ideal water conditions. This fact must be taken into consideration when a trout culture is to be installed in a calciferous country as Greece it is. In this paper a case of gas bubble disease is described in mature rainbow trouts which was appeared in Planitero village of Achaia district